GAMBARAN KEJADIAN POST PARTUM BLUES PADA IBU NIFAS DI KELURAHAN NANGGALO WILAYAH KERJA PUSKESMAS NANGGALO PADANG TAHUN 2018 - Risnawati Risnawati; Dewi Susilawati (Jurnal Kesehatan Panca Bhakti Lampung, 2018)
Postpartum blues is categorized as a mild mental disorder syndrome. Therefore, this disorder is often ignored and often even considers as a side effect of fatigue, so it is not diagnosed and not handled as it should. Finally, it can be a problem that is inciting, unpleasant, and can make uncomfortable feelings for the woman who experienced it. It is estimated that 50-70% of mothers give birth to the early symptoms of the emergence of postpartum blues, although these symptoms can disappear slowly due to the process of good adaptation and support from sufficient families. This study aims to determine the incidence of post partum blues in postpartum mothers.The type of research used is descriptive. The data collected is primary data. The population in this study were all post partum mothers on days 3 - 42 in Nanggalo Village, the working area of the Nanggalo City Health Center in Padang in June was 19 people. This research was carried out on July 2018. Data processing was done through the stages of editing, coding, entry, tabulating and cleaning which were carried out computerized. While the data analysis using univariate uses frequency distribution.Based on the results of the study found that 15.8% of respondents had a risky age, 89.5% had a low education, 73.7% of respondents did not work, 63.3% of respondents had multigravida parity and 52.6% of respondents did not experience post partum blues. Based on the results of the study found that of the 19 respondents it can be concluded as follows: more than half of the respondents had an age that was not at risk, had low education, did not work, had multigravida parity and did not experience the incidence of postpartum blues. To be expected for health workers related to postpartum maternal health should increasingly pay attention to the psychological adaptation of postpartum mothers. Keywords: Post partum blues, postpartum